SME’s Enterprise Resource Planning Implementation, Competitive Advantage, and Marketing Performance - Raharjo, Susilo Toto; -, Mudiantono; Surya Perdhana, Mirwan (Journal of Entrepreneurship, Business and Economics; Vol 4 No 1 (2016), 2016)
Enterprise Resource Planning (ERP) is an integrated application software for widespread use in the organization. The aim of this study is to determine factors that affect the successful implementation of ERP in Small and Medium Enterprises (SMEs) in Central Java in order to build competitive ad-vantage and increase marketing performance. To test the 9 hypothesis, this study utilized data from 107 SMEs in Central Java. The results revealed that variable hardware and software selection have the greatest influence toward the successful implementation in Small and Medium Enterprises. It is suggested that SMEs should gain knowledge and solidify its business process reengineering before implementing ERP. Research paper Reference to this paper should be made as follows: Raharjo, S. T., Mudiantono, Perdhana, M. S. (2016). “SME’s Enterprise Resource Planning Implementation, Competitive Advantage, and Market-ing Performance: Finding from Central Java, Indonesia”, Journal of Entrepreneurship, Business and Economics, Vol. 4, No. 1, pp. 22–44.1